The impact of oportunidades in Mexico: An integrated CGE-microsimulations modeling approach - Dorosh, Paul A.; Debowicz, Dario; Golan, Jennifer (International Food Policy Research Institute, 2011)
Conditional cash transfers (CCTs) have become a popular tool to reduce poverty and inequality in the short run and to promote investments in human capital. CCTs are now present in almost all parts of the developing world, especially in Latin America. As the name indicates, CCT programs transfer money to a targeted group conditional on the recipient's behavior, such as school attendance for children, vaccinations, health checks for infants and pregnant women, and attendance of workshops on hygiene and nutrition.Oportunidades (previously named Progresa) is a CCT program in Mexico that consists of three components: one related to education, one to health, and one to nutrition. According to Levy (2006), Oportunidades transfers represent, on average, 25 percent of household income for Mexico's rural poor and between 15 and 20 percent for the urban poor1. The program has expanded rapidly since its inception: starting from 140 thousand households in August 1997, it reached 5 million households at the beginning of 2008. Given its large size, Oportunidades is expected to have large indirect and second-round effects on the economy. To measure these effects, IFPRI researchers are using innovative modeling techniques in a project to assess the impact of Oportunidades, looking at how it has contributed to a) increasing the income of beneficiary households; b) increasing labor productivity; and c) reducing child labor in the short run.